2013
DOI: 10.3233/jad-131124
|View full text |Cite
|
Sign up to set email alerts
|

Differential Activation of mTOR Complex 1 Signaling in Human Brain with Mild to Severe Alzheimer's Disease

Abstract: Mammalian target of rapamycin (mTOR) signaling has been suggested to be effective in modifying cognitive status in animal models of Alzheimer's disease (AD), but little is known about its role in AD patients. We hereby tested whether mTOR signaling was activated and whether activated mTOR signaling was related to the degree of cognitive deficits in patients with AD. Autopsy brain hippocampal tissues were obtained from controls and patients with AD and Western blots were performed using antibodies against mTOR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(74 citation statements)
references
References 27 publications
3
71
0
Order By: Relevance
“…Unlike endosomal rabaptin5 and lysosomal Cat D, hippocampal levels of total mTOR and its active phosphorylated forms (pmTOR S2448 and pmTOR S2481) were not detectably altered in MCI or early AD. These results confirm and extend the observation that expression of mTOR and its active form pmTORs2448 in the hippocampus are stable early in the disease (present findings), whereas they are enhanced in advanced AD (33). Although the precise role of mTOR in AD pathology is still unknown, it has been reported that an increase in phosphorylated mTOR (s2481 and s2448) is associated with early tau phosphorylation in AD cortex (85, 86).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Unlike endosomal rabaptin5 and lysosomal Cat D, hippocampal levels of total mTOR and its active phosphorylated forms (pmTOR S2448 and pmTOR S2481) were not detectably altered in MCI or early AD. These results confirm and extend the observation that expression of mTOR and its active form pmTORs2448 in the hippocampus are stable early in the disease (present findings), whereas they are enhanced in advanced AD (33). Although the precise role of mTOR in AD pathology is still unknown, it has been reported that an increase in phosphorylated mTOR (s2481 and s2448) is associated with early tau phosphorylation in AD cortex (85, 86).…”
Section: Discussionsupporting
confidence: 91%
“…Reports suggest that the mammalian target of rapamycin (mTOR), a ubiquitous protein kinase, is important in autophagy regulation and tau phosphorylation (7, 32). Increased mTOR protein expression occurs in select neurons in severe AD (33), and inhibition of mTOR signaling induces autophagy, reduces tau and Aβ pathology and ameliorates behavioral deficits in young transgenic mice overexpressing Aβ and tau (3437). The signaling adaptor protein, p62, which binds raptor, an integral component of the mTORC1 pathway and interacts with tumor necrosis factor receptor-associated factor 6 (traf6), is required for mTORC1 translocation to the lysosome and its subsequent activation (38).…”
Section: Introductionmentioning
confidence: 99%
“…Mammalian target of rapamycin (mTOR) is a serine-threonine kinase that controls cell survival and growth and is often found to be dysregulated in many diseases (6,7,8). mTOR functions by forming two different protein complexes; mTORC1 and mTORC2 (9).…”
Section: Introductionmentioning
confidence: 99%
“…The weight of evidence suggests that mTOR activity is increased in the temporal cortex and hippocampus of AD patients [295,296], and an activated but dysregulated Akt/ mTOR signalling pathway in the hippocampus would appear to be a universal feature of AD and MCI (reviewed by [297]). It is noteworthy that MTOR expression is normally increasingly inhibited in the ageing brain [298,299], and hence the existence of elevated mTOR activity in the hippocampus of AD patients could be a factor underpinning dysfunctional autophagic lysosomal clearance in that region of the brain, as discussed above.…”
Section: Oxidative Stress Mtor Activation and Impaired Autophagy And mentioning
confidence: 99%